Vivência de cuidadores familiares de usuários de álcool que necessitaram de internação em terapia intensiva - Antunes, Flávia (2012)
Hospitalizations of patients with acute or chronic complications from alcohol abuse are quite common. However, hospitalization in intensive care units (ICU) is a critical and difficult experience for users of this type of drugs and for their families, because it means that the problem of alcohol abuse took a larger dimension in their lives, with the possibility of sequels and death as the outcome. An integrative review was conducted prior to the field work, using the descriptors "family" and "alcohol user" combined, showing 13 publications approaching the family relationship of alcohol users. It was a small number considering the importance of the topic, fundamental to support clinical practice and nursing care. Given these considerations, the present study aimed to understand the experience of family caregivers of patients who were alcohol users admitted to intensive care. This is an exploratory-descriptive study, carried out with patients with medical diagnoses associated with chronic or acute alcohol abuse, who were hospitalized in the adult intensive care unit of an education hospital in the Northwest of Paraná state, from January to December 2011. Data collection was conducted through semi-structured interviews with 10 family caregivers of patients. The quantitative data, for the characterization of the alcohol users, family caregivers and families were described in absolute frequency, and for the qualitative data analysis, it was used the Thematic Content Analysis. The quotidian homecare provided to alcohol users was gathered into three units of analysis ? Care given before and after hospitalization in the intensive care unit; Care given to a family member who is an alcohol abuser; Family support as a facilitator in the caregiving process. As for the feelings expressed by the family caregivers, two units of analysis were defined: Admission of alcohol users into the ICU - the pain and suffering of their family caregivers; The religiosity as a way coping the suffering. Regarding the alcohol users, most of them were male, 45.1 years average, divorced, with little schooling and unemployed. All were hospitalized due to chronic effects of alcohol intoxication, the average time of hospitalization was 40.3 days and three of them died. Five families were making less than three minimum wages of income and alcohol addiction by other members of their families was present in seven of them. The family caregivers were mostly female, usually sisters of the patients, and 46.7 years average. Seven were married and possessed low level of education. Homecare activities included surveillance and guidance for abstinence before ICU admission; care that aimed to either repair or treat the disease, immediately after discharge; surveillance activities to prevent relapse, and patient safety at the time of the interview. Caring and living with individuals addicted to alcohol was a difficult situation because their caregivers were often exposed to violence. The involvement of other family members in the caring process was an important facilitating factor for the caregiver to provide care, and despite the daily difficulties, the affection for the family outweighed the overload generated by the caregiving process. The main feelings reported by the family caregivers, regarding the admission of alcohol users in ICU, were suffering, sorrow, despair and guilt. Religiosity appeared as a way of coping with suffering. The admission of alcohol users in ICU proved to be a difficult event to be experienced by families and especially by their family caregivers, who besides the condition of living in the